Optimization of Anthocyanin Analysis Method Using LC-MS/MS to Enhance Research Service Performance at the Central Laboratory of Andalas University - Naura NADHIFAH; Alya Maghfira; Fatiyah Aghni Yati Nurmi; Daimon Syukri (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The Central Laboratory of Universitas Andalas is equipped with Shimadzu 9050 Quadrupole Time-of-Flight (QTOF) LC-MS/MS instrument, which has strong potential to support scientific research at international standards. However, the utilization of this instrument remains limited due to the lack of optimized standard methods for both qualitative and quantitative analyses. This study aims to develop an LC-MS/MS analytical method that can be used as a standard method for research services in the laboratory. The research stages included sample preparation of red flower (BM) and white flower (BP) by extraction of sample using methanol pH 3 as the solvent, separation of sample using a rotary evaporator, method optimization including selection of mobile phase composition (isocratic and binary gradient), selection of analysis time (5, 10, and 15 minutes), and optimization of collision energy in the range of 5–40. Quantitative analysis of flower samples was then conducted using the optimized method. The optimisation results showed that a binary gradient mobile-phase method with an analysis time of 15 minutes and a collision energy of 25 could be used as the analytical method. Furthermore, quantitative analysis of both flower samples revealed that cyanidin in the red flower sample was 24.92 ppm, while cyanidin in the white flower sample was 71.69 ppm. Contribution to Sustainable Development Goals (SDGs):SDG 4: Quality EducationSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production